Effects of Whole-Body Electromyostimulation on the Energy-Restriction-Induced Reduction of Muscle Mass During Intended Weight Loss - Willert, Sebastian; Weissenfels, Anja; Kohl, Matthias; von Stengel, Simon; Fröhlich, Michael; Kleinöder, Heinz; Schöne, Daniel; Teschler, Marc; Kemmler, Wolfgang (Frontiers in Physiology, 2019)
Purpose: Overweight and obesity are an increasing problem worldwide. However, most studies that focus on weight reduction by energy restriction and/or aerobic exercise reported considerable loss of muscle mass as well. Increased protein intake and/or resistance exercise might inhibit this detrimental effect during a negative energy balance. Whole-body electromyostimulation (WB-EMS), a time effective, joint-friendly, and highly customizable training technology, showed similar hypertrophic effects compared with high-intensity resistance training. The aim of this study is to evaluate the effect of WB-EMS on body composition during negative energy balance with maintained/increased protein intake in overweight premenopausal women. Patients and Methods: Ninety premenopausal, 25–50-year-old, overweight women were randomly assigned to three groups (n = 30 each). (1) Negative energy balance (−500 kcal/day) by energy restriction with compensatory protein intake (CG). (2) Negative energy balance (−500 kcal/day) by energy restriction (−250 kcal/day) and increased physical activity (−250 kcal/day) with increased protein intake (PA). (3) Negative energy balance (−500 kcal/day) due to energy restriction and increased physical activity with increased protein intake plus WB-EMS. The duration of the intervention was 16 weeks. Participants underwent restrictions in kcal per days and supplementation of protein (CG: 1.2 or PA/WB-EMS: 1.7 g/kg body mass/day) where needed. Bipolar WB-EMS was applied 1.5× week for 20 min (85 Hz; 350 μs; intermittent 6 s impulse, 4 s rest; rectangular). The primary study endpoint “lean body mass” (LBM) and secondary endpoint body fat mass (BFM) were assessed by bio-impedance analysis (BIA). Results: LBM decreased in the CG and PA group (CG: −113 ± 1,872 g; PA: −391 ± 1,832 g) but increased in the WB-EMS group (387 ± 1,769 g). However, changes were not significant (p > 0.05). Comparing the groups by ANOVA, no significant differences were observed (p = 0.070). However, pairwise adjusted comparisons determined significant differences between WB-EMS and PA (p = 0.049). BFM decreased significantly (p < 0.001) in all groups (CG: −2,174 ± 4,331 g; PA: −3,743 ± 4,237 g; WB-EMS: −3,278 ± 4,023 g) without any significant difference between the groups (ANOVA: p = 0.131). Conclusion: WB-EMS is an efficient, joint-friendly, and highly customizable training technology for maintaining muscle mass during energy restriction and can thus be considered as an alternative to more demanding resistance exercise protocols.